Catherine, Called Birdy - Cushman, Karen (New York Harper Trophy, 1994)
The thirteen-year-old daughter of an English country knight keeps a journal in which she records the events of her life, particularly her longing for adventures beyond the usual role of women and her efforts to avoid being married off
American Corner
WinnerA Newbery Honor Book
11 14
Keywords: English Fiction; English Stories